Evaluation of Static Pupil Size Using Digital Web Camera through Image Analysis (International Journal of Physiology, 2019)
IntroductionPupillometry is the measurement of pupil area or diameter which is a key parameter of routine clinical examination in wide variety of diseases. Pupillometer is a self-contained camera that objectively measures pupil diameter. Measurement of pupil area/diameter is known as pupillometry. Manual assessment can be done using pen torch which is subjective and qualitative measure. So the present study was aimed to measure the pupil size by infrared based web camera which is more accurate, repeatable and cost effective.Materials and MethodA simple web camera was used where the infrared light filter was removed from the optics so as to get image under infrared light. This camera was mounted on a stand in front of the eye at a distance of 5 cm. The recordings were done in twenty normal subjects in the age group of 18–30 years. The captured pictures were analyzed for minimum and maximum diameter of the pupil by using the ImageJ software. One time calibration for spatial measure was done prior to measurements. This was achieved by using an image of the ruler scale kept at 5 cm.ResultsMean dilated pupil diameter was 7.17 mm ± 1.38, Constricted mean diameter was 3.34mm ± 0.56.ConclusionWe have developed technique to measure the pupil diameter which is cost effective. By capturing the static pictures with help of modified web camera, it can be used to identify various clinical abnormalities reflected in pupils.